Mykhailo Ivanovich Tuhan-Baranovskyi's Concept of the Need to Introduce the Concept of “Cost” Into Scientific Circulation - Naidenov, Georgi (Research Papers, 2021)
The aim of the study is to analyze the role of Mykhailo Ivanovich Tuhan-Baranovskyi in falsifying the terminological apparatus of the classics of political economy, i.e. replacing the chain of concepts – “value”, “consumer value”, “exchange value“, “added value“, etc., with the terms – “cost“, “consumer cost“, “exchange cost“, “added cost“, etc. To achieve this goal we solved the following tasks: we showed the meaning of Tuhan-Baranovskyi's idea that in addition to the category of value, the category of “cost” should be used in Russian political economy; we studied Tuhan-Baranovskyi's theory of cost and Marx's theory of value; we considered Tuhan-Baranovskyi's critique of Marx's theory of added value. The methodological basis of the research is the materialist understanding of the historical process. The results are – “awakening” of the scientific mind of economists about the need to restore the continuity of economics. The conclusion is that Tuhan-Baranovskyi's idea to use the concept of cost not only for everyday use, but also as an economic category borrowed from Lenin, is an essential element for completely replacing the categorical apparatus of political economy.
Keywords: Terminological apparatus of political economy; Chains of concepts; Added cost; Added value; Exchange cost; Cost; Value; Exchange value